Contribution of modern seismic methods for subsurface investigations. An applicaton at Kalogreza area (Athens) - ΠΑΠΑΔΟΠΟΥΛΟΣ, Τ. Δ.; ΑΛΕΞΟΠΟΥΛΟΣ, Ι.; ΚΑΜΠΟΥΡΗΣ, Π.; ΤΟΛΗΣ, Σ.; ΚΑΒΟΥΝΙΔΗΣ, Σ. (Bulletin of the Geological Society of Greece, 2001)
In this paper the application of the seismic tomography method for subsurface investigation, especially in the case of adit detection at depths between 30 and 80 meters is presented. The use of non destructive seismic sources as the mechanical hammer as well as seismic detonators were allowed seismic waves of dominant frequency between 200Έ250 Hz to be recorded. After the processing of seismic records and the subtraction of seismic noise by applying appropriate filters, the technique of non linear inversion was elaborated by using the advanced algorithm of J. Zhang and N. Toksoz (1998). This technique was applied in three borehole pairs that were drilled in the Kalogreza area. According to the obtained results there were no large subsurface adits detected. A small differentiation in seismic velocity (of the order of 300 m/s) near boreholes Bl-1 (mainly) and Bl-3, is due either to phasies change or to different physical condition of the material.